Penerapan Sistem Proposional-Integral-Derivatif Pada Hatchery untuk Meningkatkan Produktivitas Day Old Chick (DOC) - Deni Yannuaristaa; Eko Slamet Riyadi; Nur Cholik Hasyim; Sandris Rintania (UPT Laboratorium Terpadu, Universitas Diponegoro, 2023)
The Livestock Product Processing Technology Laboratory is one of the centers of practicum, research or community service activities at the Banyuwangi State Polytechnic where it has a hatchery machine with a capacity of 500 grains, the hatchery machine has been modified so that the temperature and humidity can be controlled properly, but the machine still has some disadvantages. In addition to frequent errors in the heater, The system used still uses an on/off control system as a temperature and humidity regulator, so it can cause over shoot or under shoot which can cause fluctuations in temperature and humidity, so it is necessary to apply Proposional-Integral-Derifativ (PID) control which is able to accelerate the response of a system, eliminate offsets and produce large initial changes The purpose of this study was to determine the performance of the tool by applying PID control to hatchery machines that were tested to hatchability and Knowing the temperature and humidity settings to get the best results from the application of PID control on the hatchery machine. This research began with the preparation of the PID control series, namely making hardware and software designs using Arduino, sterilizing hatchery machines and setting temperatures of 37ºC and temperatures of 38ºC and humidity of 65 and 67%, entering eggs for 21 days and collecting data, hatchability and hatching. The results showed that PID control provided constant temperature and humidity stability at 37ºC and 38ºC temperatures, the best temperature and humidity use treatment at 38ºC was able to hatchability of 78.26%.